The Rate of Turbulent Kinetic Energy Dissipation in a Turbulent Boundary layer on a Flat Plate - Sutardi Sutardi (Institut Teknologi Sepuluh Nopember, 2014)
The rate of turbulent kinetic energy dissipation (e) is an important parameter in the turbulent flows, such as pipe flows, channel flows, atmospheric turbulence, ocean turbulence, and turbulent boundary layer flows. This study is concerning in the evaluation of the rate of turbulent kinetic energy dissipation in turbulent boundary layers developing on a flat plate. In this study, e is obtained simply from the calculation using Taylor’s frozen hypothesis. The study is performed experimentally using a low speed wind tunnel with a squared test section of 91 x 91 x 540 cm. The maximum attainable freestream velocity is approximately of 15 m/s with freestream turbulence intensity is less than 0.5%. Instantaneous fluid velocity is measured using a hot-wire anemometry system connected to a data acqusition and a personal computer. The experiments are performed at freestream velocities of 2.0 m/sec and 5.5 m/sec corresponding with momentum thickness Reynolds numbers (Rq) of approximately 1000 and 3000, respectively. The results show that maximum value of e is at approximately 1 < y+ < 10 at both Reynolds numbers. The results of e in the smooth-wall flat plate boundary layer are compared to that in the boundary layer on the flat plate modified with a square groove. There is a slight difference between e in the smooth-wall flat plate boundary layer and that in the boundary layer on the flat plate with a square groove.